'Strength becomes her' – resistance training as a route to positive body image in women. Issue 3 (26th May 2020) - Walters, Ronie; Hefferon, Kate
ABSTRACT: Physical activity has been shown to be an ideal intervention for body image and wellbeing, but very little research has focused on the role of resistance training in women, and more specifically, its role in supporting positive body image. The aim of this study was to identify the role of resistance training to positive body image in women, aged 30–55 as an under-represented demographic in this field. A qualitative approach was used and data included semi-structured interviews with 12 women from UK, USA, and New Zealand, analysed in accordance with constructivist grounded theory. The findings proposed a model of how resistance training works to foster self-efficacy and develop positive body image and psychological wellbeing. Themes that emerged included: Social and Environmental Factors, Characteristics of Resistance Training, Consequences of Resistance Training and Wellbeing Benefits. Ultimately, this research creates a springboard for future positive body image research to refine and develop ways to encourage and support more women to experience the benefits resistance training can bring.